Certainty of Promises in Housing Advertising Brochures on Home Sale and Purchase Binding Agreements - Andi Irmayanti Patta; Sabir Alwy; Oky Deviany (Al-'Adl, 2022)
This study aims to find out and analyze the legal certainty of the promises listed in the advertising brochure on the house sale and purchase agreement. This research uses normative research methods with a statute approach. the certainty of the promises of housing brochures that are part of the home sale and purchase binding agreement has the binding legal force between developers and consumers as does the law. The promises stated in the advertising brochure even if they are not contained in the binding agreement for the sale and purchase of the house must be based in good faith. Consumers have the right to get clear and correct information from the developer that the house is as promised through brochures so that consumers do not feel disadvantaged. The conses should more carefully and carefully read the brochure and the contents of the home sale and purchase binding agreement before signing the agreement.